Introduction – Peacebuilding Amidst Violence. Issue 3 (27th May 2021) - Öjendal, Joakim; Bachmann, Jan; Stern, Maria; Leonardsson, Hanna
ABSTRACT: This is a literature-reviewing and conceptualizing article introducing a Special Issue that is addressing the broad field of 'peacebuilding amidst violence'. We take as a point of departure that peacebuilding (as we know it) is widely failing to deliver on its promises. Moreover, the atypical nature and persistence of violence in post-war phases are further undermining the prospect of linear transition from war to peace as typically expected in peacebuilding ventures. We extend, however, our argument and claim that in spite of creative 'turns', the concept has exhausted its adaptive capacity, and both conceptually and empirically has few options left. We investigate the three possible, as we see it, remaining options, which all include paradigmatic changes, namely the closure of, the refusal of the failure of, and the re-enacting of, peacebuilding. Although the 're-enacting' is the preferred way forward for the authors of this introductory article, it rather opens up for the ensuing articles presented in the issue than concludes of the desirability and feasibility of that path.